2011
DOI: 10.1021/jp205759s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Secondary Electron Emission in Nanoscale Thin Metal Containing MgO Film: Laser Irradiation on Creation of F Centers

Abstract: A number of oxygen vacancies were found in the MgO film when a nanoscale-metal embedded MgO film (MgO/nanoscale metal film/MgO) was exposed to a pulsed KrF excimer laser. This was due to the interfacial reaction between embedding nanoscale metal and MgO film. In a case of Nb embedding metal, the Nb 2 O 5 crystallites were evidenced to proceed the reaction at the MgO/Nb interface; 5MgO + 2Nb f Nb 2 O 5 + 5Mg + 5V O 3 3 . The oxygen vacancies formed the F centers in the MgO bandgap, resulting in high cathodolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To clearly identify the distribution of Sn NPs, Fourier filtering was performed by masking SnO(200) (Figure 2b2) and SnO 2 (220) patterns (Figure 2b3). 36 The Fourier-filtered images and electron diffraction pattern (Figure 2b4) confirmed that SnO and SnO 2 NPs were coated on the Cu surface and had a size of 2 to 6 nm. After t c = 60 s, the TEM image (Figure 2c1) showed d spacings of 0.335, 0.264, 0.212, 0.247, and 0.181 nm, which correspond to the SnO 2 (110), SnO 2 (101), SnO 2 (210), Cu 2 O(111), and Cu(200) planes, respectively.…”
Section: Microstructure and Chemical Composition Of 3dh Cu−sn Catalys...mentioning
confidence: 74%
See 1 more Smart Citation
“…To clearly identify the distribution of Sn NPs, Fourier filtering was performed by masking SnO(200) (Figure 2b2) and SnO 2 (220) patterns (Figure 2b3). 36 The Fourier-filtered images and electron diffraction pattern (Figure 2b4) confirmed that SnO and SnO 2 NPs were coated on the Cu surface and had a size of 2 to 6 nm. After t c = 60 s, the TEM image (Figure 2c1) showed d spacings of 0.335, 0.264, 0.212, 0.247, and 0.181 nm, which correspond to the SnO 2 (110), SnO 2 (101), SnO 2 (210), Cu 2 O(111), and Cu(200) planes, respectively.…”
Section: Microstructure and Chemical Composition Of 3dh Cu−sn Catalys...mentioning
confidence: 74%
“…After coating Sn NPs on the 3D-h Cu catalyst at coating time ( t c ) = 10 s, the TEM image and electron diffraction pattern showed d spacings of 0.190, 0.168, and 0.142 nm, which correspond to the SnO(200), SnO 2 (220), and CuO(022) planes, respectively (Figure b1). To clearly identify the distribution of Sn NPs, Fourier filtering was performed by masking SnO(200) (Figure b2) and SnO 2 (220) patterns (Figure b3) . The Fourier-filtered images and electron diffraction pattern (Figure b4) confirmed that SnO and SnO 2 NPs were coated on the Cu surface and had a size of 2 to 6 nm.…”
Section: Results and Discissionmentioning
confidence: 93%
“…The other nanoscale metals as Cr, Ti, V, In, and Ta were also able to create Fs centers increasing SEEC of composite although to a lesser degree [26]. The strategy of preparing a Zn-doped MgO layer on the surface of MgO/Au composite resulted in the higher SEEC that was kept constant all the time under continuous electron bombardment of 200 eV, and this improvement was the most effective due to electrical conductivity induced by Zn doping [23].…”
Section: General Trendsmentioning
confidence: 96%
“…So, composites such as MgO/Au and Au/MgO modified by Zn and Al, showed high SEE, but despite modifying MgO, the films remained to be unstable during functioning [17][18][19][20][21][22][23][24]. The ALD fabrication of the Al 2 O 3 /MgO and MgO/Nb/MgO laminated composites with encapsulated MgO and nanoscale Nb layers was of interest for coating due to enhancement of SEEC [25,26]. This effect was explained via an occurrence of highly dispersed, conducting impurity Al particles distributed between the matrix grains [25] and via inducing the Fs center by embedded Nb metal in MgO during laser annealing [26].…”
Section: General Trendsmentioning
confidence: 99%
“…18,19 The MgO surface, which has a strong tendency to chemically bond with water molecules present in the ambient conditions by forming Mg(OH) 2 , has a low catalytic activity with carbo-hydroxyl molecules as well as low carbon solubility. 20 As a result, the MgO patterned area on Cu can be expected to have no layers of graphene. In addition, in order to obtain a at and high quality n-layer graphene surface, we have used extremely at hetero-catalytic (Ni patterned Cu foil) metal foils using the peel-off techniques based on our previous key ideas as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%